A well‐observed polar low analysed with a regional and a global weather‐prediction model. (16th March 2020) - Stoll, Patrick J.; Valkonen, Teresa M.; Graversen, Rune G.; Noer, Gunnar
Abstract: The capability of a regional (AROME‐Arctic) and a global (ECMWF HRES) weather‐prediction model are compared for simulating a well‐observed polar low (PL). This PL developed on 3–4 March 2008 and was measured by dropsondes released from three flights during the IPY‐THORPEX campaign. Validation against these measurements reveals that both models simulate the PL reasonably well. AROME‐Arctic appears to represent the cloud structures and the high local variability more realistically. The high local variability causes standard error statistics to be similar for AROME‐Arctic and ECMWF HRES. A spatial verification technique reveals that AROME‐Arctic has improved skills at small scales for extreme values. However, the error growth of the forecast, especially in the location of the PL, is faster in AROME‐Arctic than in ECMWF HRES. This is likely associated with larger convection‐induced perturbations in the former than the latter model. Additionally, the PL development is analysed. This PL has two stages, an initial baroclinic and a convective mature stage. Sensible heat flux and condensational heat release both contribute to strengthen the initial baroclinic environment. In the mature stage, latent heat release appears to maintain the system. At least two conditions must be met for this stage to develop: (a) the sensible heat flux sufficiently destabilises the local environment around the PL, and (b) sufficient moisture is available for condensational heat release. More than half of the condensed moisture within the system originates from the surroundings. The propagation of the PL is "pulled" towards the area of strongest condensational heating. Finally, the sensitivity of the PL to the sea‐surface temperature is analysed. The maximum near‐surface wind speed connected to the system increases by 1–2 m·s −1 per K of surface warming and a second centre develops in cases of highly increased temperature. Abstract : The capability of the weather‐prediction model AROME‐Arctic for simulating a well‐observed polar low is investigated. The development of this polar low is thoroughly studied by sensitivity experiments. It is found that the system has two phases, an initial baroclinic and a mature convective phase, and that the development is very sensitive to the sea‐surface temperature.